Teacher Difficulty In Compose Rubric Evaluation On Biology Learning In SMP Negeri 3 Kolaka - Niswatusyakira, Niswatusyakira; Akila, Nur; Hidayatullah, Sri Nurul; Angraini, Febrina (Journal of Biological Science and Education, 2024)
Education is an effort to change behavior which includes three aspects, namely, cognitive aspects, psychomotor aspects and affective aspects. The assessment instrument used can be an assessment rubric containing performance achievement categories.  In simple terms, a rubric is defined as an assessment reference that shows a number of criteria for displaying the process or results of students' work. The use of rubrics in assessment will provide a real picture of student abilities. This research is a qualitative descriptive type of research which aims to determine teachers' difficulties in preparing assessment rubrics. This research was carried out at SMP Negeri 3 Kolaka using the interview method with biology teachers at the school. Research results show that teachers do not experience difficulty in preparing assessment rubrics. Assessment rubrics really help teachers find out student learning outcomes. Keywords: Teacher Difficulty, Rubric, Biology Learning